The Contributions of Programming and Robotics Courses on Women's STEM Inclusion - Araujo, Thabatta Moreira Alves De; Silva, Anderson Ribeiro De Oliveira Santos; Silva, Alisson Marques Da; Maia, Eduardo Habib Bechelane; Campos, Michelli Henrique; Santos, Diego Ascanio (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
This research investigates the impact of women's involvement in STEM education through the introductory programming and robotics course offered by the Computing Department at CEFET-MG. The course aims to foster logical reasoning, creativity, and computational thinking among students in the final years of public elementary schools. The study gathered data on the participation of women as students, monitors, and researchers from 2016 to 2024. These data were organized to create graphs supporting quantitative and qualitative analyses. The results show that including women researchers in the course, which began in 2022, has positively affected young women's participation. The lack of women in the department's faculty until 2022 highlights the importance of recent efforts to promote gender diversity within the course and the wider academic environment, promoting positive practices for advancing gender equality in fields where disparities persist.